Artemether–lumefantrine treatment failure despite adequate lumefantrine day 7 concentration in a traveller with Plasmodium falciparum malaria after returning from Tanzania - Färnert Anna (Malaria Journal, 2012)
Abstract Artemether-lumefantrine is currently first-line therapy of Plasmodium falciparum malaria in many countries. This report describes a treatment failure despite adequate drug concentrations in a traveller returning from sub-Saharan Africa. Genotyping confirmed recrudescence and suggested reduced sensitivity. Potential sub-optimal effect of artemether-lumefantrine highlights the need to follow non-immune individuals the weeks after treatment.